2013
DOI: 10.7314/apjcp.2013.14.2.895
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Overexpression Inhibits Generation of Intracellular Reactive Oxygen Species and Blocks Adriamycin-induced Apoptosis in Bladder Cancer Cells

Abstract: Resistance to induction of apoptosis is a major obstacle for bladder cancer treatment. Bcl-2 is thought to be involved in anti-apoptotic signaling. In this study, we investigated the effect of Bcl-2 overexpression on apoptotic resistance and intracellular reactive oxygen species (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Leukemia types in which Bcl-2 is overexpressed have a poor prognosis and they have traditionally been related to chemoresistance, emphasizing the importance of this finding [ 7 , 39 ]. Indeed, Bcl-2 overexpression in leukemia types confers resistance to a wide range of antineoplastic drugs [ 40 44 ] and this phenomenon has also been observed in other cancers [ 11 ]. Metformin has very low toxicity and it does not affect the growth, differentiation, or survival of normal hematopoietic precursors, even at the concentrations up to 120 mM [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukemia types in which Bcl-2 is overexpressed have a poor prognosis and they have traditionally been related to chemoresistance, emphasizing the importance of this finding [ 7 , 39 ]. Indeed, Bcl-2 overexpression in leukemia types confers resistance to a wide range of antineoplastic drugs [ 40 44 ] and this phenomenon has also been observed in other cancers [ 11 ]. Metformin has very low toxicity and it does not affect the growth, differentiation, or survival of normal hematopoietic precursors, even at the concentrations up to 120 mM [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resistant phenotype represents an adaptive response of cancer cells and it is characterized by alterations to multiple pathways, among which metabolic alterations might play an important role [ 6 ]. In T-ALL, Bcl-2 overexpression or mutations in the PTEN protein are related to resistance [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral ischemia reperfusion injury is conventional case in clinical, the event can cause a large number of neuronal apoptosis, greater harm to the patients [12]. Establishing cerebral ischemia-reperfusion model, in order to simulate the human ischemia-reperfusion injury, to identify the agents can greatly reduce the cerebral ischemia injury, to reduce the suffering of patients and to improve their quality of life [13]. In this study, the suture method which establish cerebral ischemia, clinical model of infarction very similar to humans, has high research value [14].…”
Section: Discussionmentioning
confidence: 99%
“…The BAX gene expression appoints the cells' life or death decision, which is affected by ROS values. On the other hand, an anti‐apoptotic gene called BCL2 makes the cell capable of bypass apoptotic death under different destructive stresses . M. Song et al demonstrated the significant BCL2 down‐regulation in the presence of vitamin C (strong antioxidant agent).…”
Section: Introductionmentioning
confidence: 99%